Body mass index mediates the effect of the DASH diet on hypertension: Common metabolites underlying the association. Issue 1 (26th October 2021) - Louca, Panayiotis; Nogal, Ana; Mompeo, Olatz; Christofidou, Paraskevi; Gibson, Rachel; Spector, Tim D.; Berry, Sarah E.; Valdes, Ana M.; Mangino, Massimo; Menni, Cristina
Abstract: Background: The Dietary Approaches to Stop Hypertension (DASH) diet is beneficial in reducing blood pressure; however, this may be a consequence of concurrent weight reduction. In the present study, we investigated whether body mass index (BMI) mediates the association between the DASH diet and hypertension and investigate common metabolic pathways. Methods: We included 2424 females from the cross‐sectional TwinsUK cohort, with blood pressure, BMI and dietary intake measured within 1.01 (SD = 0.68) years and serum metabolomics profiling (591 metabolites). We constructed a mediation model to test the mediation effects of BMI on the total effect of the DASH diet on hypertension. To identify a metabolite panel associated with the DASH diet and BMI, we built random forest models for each trait, and selected the common metabolic contributors using five‐fold cross‐validation error. Results: We found that BMI fully mediates the association between the DASH diet and hypertension, explaining 39.1% of the variance in hypertension. We then identified a panel of six common metabolites predicting both the DASH diet and BMI with opposing effects. Interestingly, at the univariate level, the metabolites were also associated with hypertension in the same direction as BMI. The strongest feature, 1‐nonadecanoyl‐GPC (19:0), was positively associated with the DASH diet (β [SE] = 0.65 [0.12]) and negatively with BMI (β [SE] = −1.34 [0.12]) and hypertension (odds ratio = 0.71, 95% confidence interval = 0.6–0.84). Conclusions: We highlight the role of BMI in the mechanisms by which the DASH diet influences hypertension and also highlight common metabolic pathways. Further studies should investigate the underlying molecular mechanisms to increase our understanding of the beneficial ways of treating hypertension. Abstract : Key points: Adherence to the DASH diet can reduce blood pressure; however, this may be a consequence of concurrent weight reduction. In a large sample of 2424 females from TwinsUK, we report that BMI fully mediates the association between the DASH diet and hypertension, explaining 39.1% of the variance in hypertension. We also identify a panel of six common metabolites predicting both the DASH diet and BMI with opposing effects, highlighting common metabolic pathways. Further studies should investigate the underlying molecular mechanisms to increase our understanding of the beneficial ways of treating hypertension.